Validation of Numerical Approach for the Analysis of Adhesively-bonded Scarf Joints - D. F. O. Silva; R. D. S. G. Campilho (Technological Innovation in Engineering Research Vol. 7, 2022)
Cohesive Zone Model (CZM) is the numerical technique most frequently used for adhesive bonds. This work consists of a validation of CZM laws in traction and shear, estimated by the application of the direct method, in the strength prediction of joints under a mixed-mode loading. In this chapter, adhesives of various ductilities and scarf joints with various scarf angles (\(α\) ) were examined. Simplified triangular, trapezoidal, and exponential laws were developed and evaluated for each of the adhesives on the basis of pure-mode cohesive laws. By contrasting the numerical predictions with the outcomes of the experiments, their validity was established. By using the direct method, it was possible to produce extremely accurate predictions for the maximum load (Pm), which showed that cohesive law shape was best for each adhesive/geometry combination. This analysis has led to the conclusion that no significant Pm mistakes are incurred by the selection of a less appropriate law.